(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nurses play a multifaceted and indispensable role in modern healthcare delivery, extending beyond conventional clinical boundaries to provide holistic and patient-centered care. This paper explores the distinctive contributions of nurses, emphasizing their essential role in promoting health, preventing illness, and alleviating suffering. Through a review of literature and case studies, it highlights key nursing competencies such as patient advocacy, care coordination, and health education. Furthermore, it examines the collaborative dynamics between nurses and other healthcare professionals, particularly doctors, stressing the significance of effective communication and interdisciplinary teamwork in optimizing patient outcomes.